2022
DOI: 10.1186/s12905-022-01830-x
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence and associated factors among reproductive age women in Liberia: a cross-sectional study using a recent Liberian demographic and health survey

Abstract: Background Intimate partner violence (IPV) is a major public health problem and a violation of women's human rights. Almost one third of women aged 15–49 years who have been in a relationship have experienced to some form of physical and/or sexual violence by their intimate partner worldwide. Objective The study aimed to assess the prevalence of intimate partner violence within the last 12 months and associated factors among reproductive aged women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
3
2
1
Order By: Relevance
“…Similar findings showing that women from households in the higher wealth spectrum (richer or richest) were less likely to experience IPV and to be underweight is in line with findings from a study conducted in Bangladesh [24]. Also, the findings of the present study indicating that women who live in urban areas, those who have attained secondary education, those from middle wealth quintile households, working women and those who read newspaper and watch television, are less likely to simultaneously suffer from IPV and underweight are consistent with similar findings in Uganda and elsewhere [25][26][27][28][29]. These findings emphasize the role higher education, high PLOS GLOBAL PUBLIC HEALTH levels of socio-economic status and access to mass media play in empowering women and protecting them against human rights violations such as IPV.…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings showing that women from households in the higher wealth spectrum (richer or richest) were less likely to experience IPV and to be underweight is in line with findings from a study conducted in Bangladesh [24]. Also, the findings of the present study indicating that women who live in urban areas, those who have attained secondary education, those from middle wealth quintile households, working women and those who read newspaper and watch television, are less likely to simultaneously suffer from IPV and underweight are consistent with similar findings in Uganda and elsewhere [25][26][27][28][29]. These findings emphasize the role higher education, high PLOS GLOBAL PUBLIC HEALTH levels of socio-economic status and access to mass media play in empowering women and protecting them against human rights violations such as IPV.…”
Section: Discussionsupporting
confidence: 92%
“…This study also found that the odds of accessing healthcare were high among rich households as compared to poor household wealth status. This result is consistent with studies conducted in Ethiopia [22,24,25,31,47], Gambia [36], Myanmar [29], Tanzania [6], and SSA [19,26]. The possible explanation might be due to a rich wealth index may reduce the difficulties of obtaining money to access health care [20].…”
Section: Discussionsupporting
confidence: 90%
“…The current study finding showed a lower magnitude of access to healthcare than study reports in SSA [26], Ethiopia [31], Vermont [23], Gambia [36], and Myanmar [29]. The difference in the study population might be the reason for the variation.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Motivated by the necessity to address this global problem, quantitative research investigates the determinants of IPV in developing countries. Studies highlight sociodemographic factors like women's education ( Ahinkorah et al, 2018 ; Oluwagbemiga et al, 2023 ; Rahman et al, 2020a ), women's age at marriage ( Murshid, 2017 ; Terrazas-Carrillo & McWhirter, 2015 ; Tsegaw et al, 2022 ), and exposure to violence during childhood ( Abramsky et al, 2011 ; Murshid & Murshid, 2018 ). Studies also highlight contextual factors like patriarchal norms ( Heise & Kotsadam, 2016 ; Murshid & Critelli, 2020 ), religious fractionalization ( Kaya & Cook, 2010 ), and community inequality ( Munguia & Martinez-Zarzoso, 2022 ).…”
Section: Introductionmentioning
confidence: 99%